Diseño de mezclas concreto fast track en reparación y rehabilitación de pavimentos en la ciudad de Arequipa - Daniela Paliza Florez (2017)
The rapid technique of enabling traffic using the Fast Track concrete arises from the need to repair and rehabilitate pavements in poor state of operation in the shortest possible time. The purpose of the study is to propose the Fast Track system as an alternative for the repair and rehabilitation of pavements, obtaining mix designs with a resistance greater than 280 kg / cm2 at an age of 8, 12 and 24 hours. In the following investigation, mix designs were compared to low A / C, using the Fineness Modulus method, with different types of cements which are HE, IP, IP adding with Ultraval and Type I, with the addition of superplasticizer additives And forging accelerator if required, the curing was performed using a chamber with fiberglass blankets. For the quality control of Fast Track concrete, several tests were carried out on fresh and hardened concrete. According to the results obtained, we verified that our designs meet the requirements for the early opening of a track. Through the research it has been concluded that it is possible to obtain mix designs with a compressive strength greater than 280 kg / cm2 with a modulus of breakage greater than 38.6 kg / cm2 at an age of 8,12 and 24 hours